Reproductive Phases Influence on In Vitro Maturation of Abattoir-Derived Bovine Oocytes - Das, Z C; Rashid, MM; Hoque, MN; Haider, MG; Talukder, AK; Rahman, ANMA (Annals of Bangladesh Agriculture, 2022)
This study investigated the influence of the reproductive phase of oocyte donors originating from abattoir-derived ovaries on in vitro maturation (IVM) of bovine oocytes. The IVM of the oocytes was evaluated by observing the degree of cumulus cell (CC) expansion and extrusion of the first polar body (PB-1) as well as both nuclear progression (NP) and cytoplasmic maturation (CM). For NP, after 24 h of IVM, oocytes were denuded and stained with DNA fluorochrome and observed under an epifluorescence microscope. The male or female pronucleus (PN) forming ability of an oocyte following in vitro fertilization (IVF) was considered as CM. For CM, the fertilized zygotes after 24 h post-insemination were stained with DNA fluorochrome and observed under an epifluorescence microscope. Results revealed that the maturation rate was significantly influenced by the reproductive phase of the oocytes donor, luteal phase ovaries (LPO) versus follicular phase ovaries (FPO) based on the presence or absence of corpus luteum (CL), respectively. The significantly higher CC expansion (2°; 44.9±4.9% versus 35.9±2.7%) and PB-1 extrusion (58.3±1.7% versus 46.7±2.4%) were observed with LPO than FPO oocytes, respectively. A significant (p<0.05) effect of the reproductive phase was also noted with LPO oocytes progressing higher rate of mature metaphase II stage (MII; 58.3±1.7% versus 46.7±2.4%) and PN (54.9±2.3% versus 44.4±3.0%) formation following IVF than FPO oocytes that imply better NP and CM of oocytes, respectively. Therefore, the present study indicates that the reproductive phase of oocyte donors notably from LPO positively influences the IVM of bovine oocytes to produce a higher number of viable embryos in vitro. Ann. Bangladesh Agric. (2022) 26 (1) : 1-19